2015
DOI: 10.1108/ijopm-07-2013-0356
|View full text |Cite
|
Sign up to set email alerts
|

Operations strategies of engine assembly plants in the Brazilian automotive industry

Abstract: Purpose – The purpose of this paper is to identify and analyze the operations strategies (OSs) adopted by six of the all seven automobile engine manufacturers in action in Brazil during the years of 2005 and 2006. Design/methodology/approach – Semi-structured interviews were held with at least one of the top managers at each engine manufacturing plant to collect information about the aforementioned strategies. The questions were aimed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…The building blocks of the manufacturing and supply chain flexibility competence are the interconnected and reinforcing approaches to planning (the planning cluster), partners -in procurement (the purchasing cluster) and distribution (the distribution and MSCF sub-cluster) -, the processes that build manufacturing flexibility and finally information sharing and communication (the collaboration and MSCF sub-cluster) These can be considered as the key structural and infrastructural building blocks of manufacturing and supply chain flexibility (Slack 2005a;Merschmann and Thoneman 2011;Alves-Filho et al 2015). It is worth noting that these building blocks are still predominantly considered in isolation (Li et al 2018), providing opportunities for integrative studies (Kumar and Mishra 2017;Singh and Kumar 2017).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…The building blocks of the manufacturing and supply chain flexibility competence are the interconnected and reinforcing approaches to planning (the planning cluster), partners -in procurement (the purchasing cluster) and distribution (the distribution and MSCF sub-cluster) -, the processes that build manufacturing flexibility and finally information sharing and communication (the collaboration and MSCF sub-cluster) These can be considered as the key structural and infrastructural building blocks of manufacturing and supply chain flexibility (Slack 2005a;Merschmann and Thoneman 2011;Alves-Filho et al 2015). It is worth noting that these building blocks are still predominantly considered in isolation (Li et al 2018), providing opportunities for integrative studies (Kumar and Mishra 2017;Singh and Kumar 2017).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…For example, Peng et al [95] noted that emphasizing competitive priorities such as quality and delivery should be a driver of decisions relating to management practices. In addition, the study by Filho et al [96] identified factors including teamwork, multiple skills and education as important structural areas to be developed in the pursuit of competitive priorities such as delivery. The study by Yen and Sheu [97] went further and found a medium to high association between the competitive priority of delivery and labor skills.…”
Section: The Relationships Between Competitive Priorities and Employee Management And Developmentmentioning
confidence: 99%
“…Different manufacturing choices are required for different missions, and the focus and choices need to change in accordance with changes in markets, products or technology (Hayes et al, 2005). Manufacturing choices may also affect one other, as well as competitive priorities (Alves Filho et al, 2015).…”
Section: Decision Categoriesmentioning
confidence: 99%
“…Since Hayes and Wheelwright (1984) introduced the concept of decision categories, numerous researchers have contributed to the development of these categories (e.g., Leong et al, 1990;Olhager and Rudberg, 2002;Dìaz Garrido et al, 2007;Alves Filho et al, 2015). Decision categories are divided into structural and infrastructural categories, as proposed by Hayes and Wheelwright (1984).…”
Section: Decision Categoriesmentioning
confidence: 99%